The Rewards of Fiscal Consolidation : Sovereign Spreads and Confidence Effects - David, Antonio (IMF Working Papers; Working Paper ;, 2019)
This paper investigates the effects of fiscal consolidation announcements on sovereign spreads in a panel of 21 emerging market economies during 2000-18. We construct a novel dataset using a global news database to identify the precise announcement date of fiscal consolidation actions. Our results show that sovereign spreads decline significantly following news that austerity measures have been approved by the legislature (congress or parliament), in periods of high sovereign spreads or in countries under an IMF program. In addition, consolidation announcements are less contractionary when sovereign spreads decline, with the reduction in output being half of the counterfactual case in which spreads do not respond to announcements. These results constitute direct evidence that confidence effects, in the form of lower sovereign spreads, are an important transmission channel of fiscal shocks. We also find that the role of confidence effects increases with the level of spreads such that countries with high spread levels stand to benefit the most from putting in place credible austerity packages.